Abnormalities in enamel structure and their association with systemic diseases and syndromes - Jeremić Marko; Marković Dejan; Vuković Ana; Babić Marko; Jokanović Vukoman (Serbian Medical Society - Dental Section, Belgrade, 2011)
Etiology of abnormalities in tooth structure has been subject of numerous studies but still has not been fully understood. Heredity is an established etiological factor for many types of structural anomalies of the teeth. Factors that cause changes in enamel structure may be genetic, immunologic and teratogenic or systemic diseases. Genetic changes may include individual genes, micro deletions or chromosomal defects. Systemic diseases can be associated with anomalies of tooth structure and diversity of clinical picture requires a multidisciplinary approach to the therapy. Amelogenesis imperfecta (AI) represents a large group of structural abnormalities of the teeth. AI can exist independently or as a part of large number of syndromes and systemic diseases. Knowledge of clinical presentation, etiology, pathogenesis of structural anomalies of the teeth and their association with certain systemic diseases is of great importance to everyday dental practice in terms of prevention, prognosis and therapy. Also, it is necessary to expand basic knowledge of pediatricians in regards to the clinical picture of anomalies in tooth structure and their possible association with a wide range of systemic diseases and syndromes, in order to provide comprehensive clinical treatment. Therefore, the aim of this study was to present etiopathogenesis and classification and to describe the most important abnormalities of enamel structure and their association with systemic diseases and syndromes.